Land Use mix and Daily Mobility - the Case of Bordeaux, France - Guillaume Pouyanne (European Regional Science Association (ERSA), 2005)
The influence of land use on daily mobility patterns can be described by the two dimensions of urban form : the first is quantitative, that is density, and the second is qualitative, that is land use mix. Empirical studies usually add control variables such as socio-demographic characteristics. They suppose that urban form factors and socio-demographic factors have a separate influence on travel patterns. In this paper, we first show the possibility of a causal relationship between urban form and socio-demographic characteristics. Thus previous results, which suppose that these two kinds of factors are separated, may be biased. As a consequence we provide a new, more complex conceptual framework, which is called the « triangular relationship ». It implies specific econometric methods to test the motives of mobility : typological regressions are used for an application on the metropolitan area of Bordeaux. First results show how relevant this method is for the study of the interactions between land use and travel patterns.
Keywords: 330